Dumped : a grown-up guide to gettin' off your ass and over your ex in record time - Fahey, Maryjane (Sellers Pub., 2012)
This smart, sassy, and visually fun book will inspire women to take charge of their lives, get over their exes, get off their asses and have fun! Includes the authors' own personal stories, advice from other women who've been dumped, and practical recommendations on where to go and what to do to get your life back on track.